Exploring the relationships between eco-anxiety, eco-guilt, eco-grief, and pro-environmental behavior in the Dutch and German population: A cross-sectional study - Michele Petkovski; Johannes Steinrücke; Alejandro Dominguez-Rodriguez (PLoS ONE, 2026)
While experiencing individual eco-emotions, such as eco-anxiety, eco-guilt, and eco-grief, has been linked to pro-environmental behavior, no prior studies have jointly investigated these variables. Research in Dutch and German populations is particularly scarce despite being at relatively high risk for experiencing the effects of climate change, such as floods. This study examined the relationship between eco-anxiety and pro-environmental behavior, with eco-guilt and eco-grief as mediators, and age, gender, and proximity to water as moderating variables. Cross-sectional data ( n = 311) were collected using an online survey. Data analyses revealed significant positive correlations between all three eco-emotions and pro-environmental behavior. A positive relationship between eco-anxiety and pro-environmental behavior was found, which was mediated by eco-guilt, but not eco-grief. With a negative indirect effect of eco-guilt on pro-environmental behavior, eco-guilt was a non-linear, suppressor-like variable. Only age moderated the pathway from eco-anxiety to eco-guilt; no moderation effects were found for gender or proximity to water. This research provides preliminary evidence of the complex relationships between eco-anxiety, eco-guilt, eco-grief, and pro-environmental behavior in a Dutch and German population. The findings highlight the importance of developing educational programs to inform individuals about eco-emotions and potential coping strategies, while promoting pro-environmental behavior. Future studies with larger, more diverse samples are recommended to replicate the results and explore which groups of individuals may be more vulnerable to experiencing higher levels of eco-emotions. Further, intensive longitudinal research designs combined with (generalized) causal mediation analyses could be applied to unravel the temporal interplay of eco-emotions and PEB.